Economic impact of potentially inappropriate prescribing and related adverse events in older people: a cost-utility analysis using Markov models - Kathleen Bennett; Frank Moriarty; Tom Fahey; Caitriona Cahir (BMJ Open)
Objectives To determine the economic impact of three drugs commonly involved in potentially inappropriate prescribing (PIP) in adults aged ≥65 years, including their adverse effects (AEs): long-term use of non-steroidal anti-inflammatory drugs (NSAIDs), benzodiazepines and proton pump inhibitors (PPIs) at maximal dose; to assess cost-effectiveness of potential interventions to reduce PIP of each drug.Design Cost-utility analysis. We developed Markov models incorporating the AEs of each PIP, populated with published estimates of probabilities, health system costs (in 2014 euro) and utilities.Participants A hypothetical cohort of 65 year olds analysed over 35 1-year cycles with discounting at 5% per year.Outcome measures Incremental cost, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios with 95% credible intervals (CIs, generated in probabilistic sensitivity analysis) between each PIP and an appropriate alternative strategy. Models were then used to evaluate the cost-effectiveness of potential interventions to reduce PIP for each of the three drug classes.Results All three PIP drugs and their AEs are associated with greater cost and fewer QALYs compared with alternatives. The largest reduction in QALYs and incremental cost was for benzodiazepines compared with no sedative medication (€3470, 95% CI €2434 to €5001; −0.07 QALYs, 95% CI −0.089 to –0.047), followed by NSAIDs relative to paracetamol (€806, 95% CI €415 and €1346; −0.07 QALYs, 95% CI −0.131 to –0.026), and maximal dose PPIs compared with maintenance dose PPIs (€989, 95% CI -€69 and €2127; −0.01 QALYs, 95% CI −0.029 to 0.003). For interventions to reduce PIP, at a willingness-to-pay of €45 000 per QALY, targeting NSAIDs would be cost-effective up to the highest intervention cost per person of €1971. For benzodiazepine and PPI interventions, the equivalent cost was €1480 and €831, respectively.Conclusions Long-term benzodiazepine and NSAID prescribing are associated with significantly increased costs and reduced QALYs. Targeting inappropriate NSAID prescribing appears to be the most cost-effective PIP intervention.